Research on emergency rescue technology and equipment for train operation accidents on a heavy-haul railway network. Issue 4 (27th June 2020) - Zhou, Xianping; Wei, Xiang; Ma, Lin; Bai, Fuwei; Huang, Hongwei
Abstract: Bridges, tunnels, cuttings and high subgrade account for a relatively large proportion in China's heavy-haul railway system, where 10 000 t of unit trains and 20 000 t of combined trains are in operation. When a train operation accident occurs, it can easily cause vehicle intrusions, slant-span lines, tipping and stacking. Based on the viewpoint of system engineering, rescue methods such as hoisting, lifting, pulling and overturning are integrated, according to the characteristics of heavy-haul transport and the construction practice of train accident rescue system. A scheme of technical research and equipment configuration relating to heavy-haul railway rescue in China is put forward based on the situation—embankment, bridge, tunnel (including cuttings), ramp and curve rescue, and so on—and three-dimensional finite-element modelling and calculation checks on the key components are carried out.